EFEKTIVITAS EKSTRAK BAWANG PUTIH TERHADAP MORTALITAS Sitophilus zeamais M. PADA JAGUNG DI PENYIMPANAN - Hasnah Hasnah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
ABSTRACT The objective of study was to determine the effective concentration of garlic extract in controlling S. zeamais on maize in storage. Concentrations of garlic extract tested were 2 percent, 4 percent, 6 percent, 8 percent, 10 percent, and 12 percent. The results showed that garlic extracts were potential as plant-based insecticide, indicated by a positive effect of garlic extract on S. zeamais mortality, the average time of S. zeamais death, the maize kernel damage and the number of S. zeamais progeny. Concentration of 12 percent gave the highest mortality rate of S. zeamais, the fastest average time of S. zeamais death, the lowest maize kernel damage and the lowest number of S. zeamais progeny, while the concentration of 2 percent gave the lowest mortality rate of S. zeamais, the longest average time of S. zeamais death, the highest percentage of kernel damage, and the highest number of S. zeamais progeny.